Establishing a method to support academic and professional competence throughout an undergraduate radiography programme - Ng, Curtise Kin Cheung; White, P.; McKay, Jan (Elsevier Ltd, 2008)
Purpose: Radiography degree programmes are coming under increasing pressurefrom the community to ensure that graduates have not only the necessary academic developmentbut also the practice-based skills. This study aims to establish a method of monitoringstudents’ progress towards, and ability to meet, academic and professional competencesthroughout a radiography programme.Methods: Questionnaires were designed for students and academic staff to determine thestages and standards of progress of competence development, and to inform the review processof the current assessment tools throughout the programme. A literature search identifiedthe appropriate pedagogy as a basis for devising the method. Another questionnaire was distributedto overseas radiography institutions to gain insights into other assessment practicesto validate the framework.Results and discussion: It was established that years of study rather than semester periodswere appropriate to allow students to meet the standards. Discrepancies were noted in theexpectations between academic staff (higher expectations) and students (more realistic) interms of the pace of development expected. As students progress at different rates, and donot experience the same clinical exposure, their ability to meet expectations may differand so both sets of expectations were combined as a range of criteria. A multi-dimensionalassessment approach should be adequate to gauge students’ progress but time and resourceeffectiveness has not yet been addressed. The portfolio was identified as the pedagogy capableof integrating all the competence assessment tools, linked by reflective writing, to gatherindividual outcomes into a whole, and form a holistic framework.Outcome: The portfolio framework will initially run as a voluntary activity and standards ofprogress corresponding to the students’ stages will be delivered to participants in advance.Participants will be required to select materials and reflect on these, as evidence of development.Faculty members will provide support and feedback to students and oversee the wholeprocess.